When does the parliamentary opposition take to the streets? Social protest against government COVID-19 policy. - Martínez Fuentes, Guadalupe; Natera, Antonio (West European Politics, 2025)
This article identifies the conditions that made parliamentary oppositions in democratic countries more or less likely to participate in social protests against their government's COVID-19 policies from 2020 to 2021. To that end, it compares 19 cases, testing the explanatory power of causal configurations consisting of four factors. The first is the parliamentary opposition's level of power in the policy-making process. The second concerns the political-electoral moment in which the protests take place. The third and fourth refer, respectively, to the representation or non-representation of populist and far-right forces amongst the parliamentary opposition. The finding is that the parliamentary opposition's involvement in social protests is due to different causal configurations. It occurred when some kind of non-far-right populism was represented in the parliamentary opposition, the parliamentary opposition had a low level of policy-making power and the protests could be exploited for electoral gain. Another explanation is the representation of populists who are also far right amongst the parliamentary ranks, even when the other conditions are not the most favourable in terms of the political moment and the level of institutional power of the opposition.